A kinetic model of GPCRs: analysis of G protein activity, occupancy, coupling and receptor-state affinity constants. (4th July 2015) - Stein, Richard S. L.; Ehlert, Frederick J.
Abstract: Context : G protein-coupled receptors are vital macromolecules for a wide variety of physiological processes. Upon agonist binding, these receptors accelerate the exchange of GDP for GTP in G proteins coupled to them. The activated G protein interacts with effector proteins to implement downstream biological functions. Objective : We present a kinetic, quaternary complex model, based on a system of coupled linear first-order differential equations, which accounts for the binding attributes of the ligand, receptor, G protein and two types of guanine nucleotide (GDP and GTP) as well as for GTPase activity. Methods : We solved the model numerically to predict the extents of G protein activation, receptor occupancy by ligand and receptor coupling that result from varying the ligand concentration, presence of GDP and/or GTP, the ratio of G protein to receptor and the equilibrium constants governing receptor pre-coupling and constitutive activity. We also simulated responses downstream from G protein activation using a transducer function. Results : Our model shows that agonist-induced G protein activation can occur with either a net decrease or increase in total receptor-G protein coupling. In addition, we demonstrate that affinity constants of the ligand for both the active and inactive states of the receptor can be derived to a close approximation from analysis of simulated responses downstream from receptor activation. Discussion and conclusion : The latter result validates our prior methods for estimating the active state affinity constants of ligands, and our results on receptor coupling have relevance to studies investigating receptor-G protein interactions using fluorescence techniques.